Checklist of the shallow-water marine Brachyura (Crustacea: Decapoda) of Barbados, West Indies - Parasram, Nadeshinie; Santana, William; Vallès, Henri (Zootaxa, 2023)
Here we provide an illustrated and annotated checklist of brachyuran crabs associated with shallow water marine habitats (nearshore rubble and subtidal) in Barbados, West Indies (13.1939°N, 59.5432°W). Twenty-one (21) survey sites in nearshore rubble and shallow subtidal habitats were surveyed between October 2018 to September 2021. Nearshore rubble habitats were surveyed at low tide during the day and night periods. Shallow nearshore subtidal habitats were surveyed every 9–12 days from February to October 2019 using crab traps placed ~ 4 m deep on sandy and rocky bottoms. A total of 1,640 specimens were recorded, belonging to nine (9) superfamilies, 14 families, 34 genera, and 44 species. The genera Charybdis De Haan, 1833, Pitho Bell, 1835, Thoe Bell, 1835, and Uhlias Stimpson, 1871 are here reported for the first time for Barbados. Thirteen (13) species are first records for Barbados, thus extending their geographic range. The most abundant and widespread species collected was Mithraculus coryphe Herbst, 1801, which accounted for 35% (N = 570) of the specimens, occurring in both nearshore rubble and subtidal habitats.